Biomechanical Analysis of Human Gait When Changing Velocity and Carried Loads: Simulation Study with OpenSim - Cristina Brambilla; Giulia Beltrame; Giorgia Marino; Valentina Lanzani; Roberto Gatti; Nicola Portinaro; Lorenzo Molinari Tosatti; Alessandro Scano (Biology, 2024)
Walking is one of the main activities of daily life and gait analysis can provide crucial data for the computation of biomechanics in many fields. In multiple applications, having reference data that include a variety of gait conditions could be useful for assessing walking performance. However, limited extensive reference data are available as many conditions cannot be easily tested experimentally. For this reason, a musculoskeletal model in OpenSim coupled with gait data (at seven different velocities) was used to simulate seven carried loads and all the combinations between the two parameters. The effects on lower limb biomechanics were measured with torque, power, and mechanical work. The results demonstrated that biomechanics was influenced by both speed and load. Our results expand the previous literature: in the majority of previous work, only a subset of the presented conditions was investigated. Moreover, our simulation approach provides comprehensive data that could be useful for applications in many areas, such as rehabilitation, orthopedics, medical care, and sports.